2021
DOI: 10.1111/1751-7915.13871
|View full text |Cite
|
Sign up to set email alerts
|

Strain diversity of plant‐associated Lactiplantibacillus plantarum

Abstract: Lactiplantibacillus plantarum (formerly Lactobacillus plantarum) is a lactic acid bacteria species found on plants that is essential for many plant food fermentations. In this study, we investigated the intraspecific phenotypic and genetic diversity of 13 L. plantarum strains isolated from different plant foods, including fermented olives and tomatoes, cactus fruit, teff injera, wheat boza and wheat sourdough starter. We found that strains from the same or similar plant food types frequently exhibited similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 93 publications
2
29
0
Order By: Relevance
“…Lactiplantibacillus plantarum is a model species for research in lactobacilli, which comprise an important group of probiotics for both humans and animals ( Martino et al, 2016 ; Choi et al, 2018 ; Teame et al, 2020 ; Yu et al, 2020 , 2021 ). L. plantarum strains have diverse phenotypes and genotypes that facilitate a metabolic flexibility that allow them to colonize a variety of environments, including the human gastrointestinal tract ( Pretzer et al, 2005 ; Marco et al, 2010 ; Fidanza et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lactiplantibacillus plantarum is a model species for research in lactobacilli, which comprise an important group of probiotics for both humans and animals ( Martino et al, 2016 ; Choi et al, 2018 ; Teame et al, 2020 ; Yu et al, 2020 , 2021 ). L. plantarum strains have diverse phenotypes and genotypes that facilitate a metabolic flexibility that allow them to colonize a variety of environments, including the human gastrointestinal tract ( Pretzer et al, 2005 ; Marco et al, 2010 ; Fidanza et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that various phenotypic and genotypic methods, such as MLST, Asc I-PFGE, and WGS, allow L. plantarum to be typed at the interspecies and intraspecies levels ( Guidone et al, 2014 ; Martino et al, 2016 ; Evanovich et al, 2019 ; Manzoor and Tayyeb, 2019 ; Yu et al, 2021 ). Although these methods have completely updated our understanding of the bacterial population structure, they ignore the phenotypic variations caused by certain genetic changes, especially genotypic or phenotypic characteristics related to key macromolecules on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of these strains significantly influenced the results. C. apicola and C. atlantica were identified in brines [54] and as part of cheese micro-flora in cheese with a long ripening period (up to 60 days) [55,56]. However, their effect on cheeses is not confirmed to be detrimental.…”
Section: The Sensitivity Of Yeast Strainsmentioning
confidence: 99%
“…This result shows how these bacteria have adapted for coexistence in that environment. The capacity for the single macronutrient calcium to restore B1.3 competitive fitness in laboratory culture medium suggests that L. plantarum intraspecies diversity found in food systems is fine-tuned to nutrient requirements at the strain level.Recent comparative genomic analysis and phenotypic screening approaches have shown the tremendous intraspecific variation in the L. plantarum species (14,19,20). We recently reported that L. plantarum from the same (fermented) plant food type tend to use the same carbohydrates for growth and exhibit similar stress tolerance levels, indicating the presence of strong selective pressures for strain selection and adaptation within those environments (20).However, despite certain similarities, strain variation is not limited to isolation source, and we and others showed that L. plantarum strains recovered from the same food, plant, or animal environment can have very different genotypic and phenotypic properties (19).…”
mentioning
confidence: 99%